What is Financial Therapy? Discovering Mechanisms and Aspects of an Emerging Field - Kristy L Archuleta; Emily A Burr; Anita K Dale; Anthony Canale; Dan Danford; Erika Rasure; Jeff Nelson; Kelley Williams; Kurt Schindler; Brett Coffman; Ed Horwitz (Journal of Financial Therapy, 2012)
Very little research currently exists specifically on the topic of financial therapy. In this emerging field, it is important to lay the groundwork for future practice and study. The purpose of this study was to answer the question, “What are the mechanisms and aspects of financial therapy?” Using qualitative methods, eighteen members of the Financial Therapy Association were interviewed by members of the research team. The participants included six financial professionals, six mental health professions, and six researchers/educators all engaged in financial therapy. Six categories emerged from the analysis of data, including: (a) integration, (b) complexity, (c) help seeker issues, (d) helper issues, (e) process, and (f) research. The analysis resulted in a conceptual framework and ten theoretical assumptions of financial therapy.
Keywords: financial therapy